Comparison between IgG and F(ab′)2 polyvalent antivenoms: neutralization of systemic effects induced by Bothrops asper venom in mice, extravasation to muscle tissue, and potential for induction of adverse reactions - León Montero, Guillermo (2001)
Whole IgG and F(ab′)2 equine-derived polyvalent (Crotalinae) antivenoms, prepared from the same batch of hyperimmune plasma, were compared in terms of neutralization of the lethal and defibrinating activities induced by Bothrops asper venom, their ability to reach the muscle tissue compartment in envenomated mice, and their potential for the induction of adverse reactions. Both preparations were adjusted to the same potency against the lethal effect of B. asper venom in experiments involving preincubation of venom and antivenom. Then, “rescue” experiments were performed, i.e. antivenom was administered either intravenously or intramuscularly at various times after envenomation. IgG and F(ab′)2 antivenoms were equally effective in the neutralization of lethality, both being more effective when administered i.v. than after i.m. injection. Neutralization decreased as the time lapse between envenomation and treatment increased. No significant differences were observed in the ability of antivenoms to neutralize defibrinating activity of B. asper venom in experiments involving independent injection of venom and antivenoms. There was a much higher accumulation of equine antibodies in muscle tissue that had been injected with B. asper venom than in non-envenomated tissue, indicating that venom-induced microvessel damage probably favors a prominent and similar extravasation of both IgG and F(ab′)2 antibodies. This may explain the similar effectiveness of both types of antivenom in previously reported studies on the neutralization of venom-induced local tissue damage. Both IgG and F(ab′)2 antivenoms activate human complement in vitro and induce an anti-equine immunoglobulin response in mice, indicating that Fc removal per se does not eliminate the potential for inducing adverse reactions. However, IgG antivenom had higher anticomplementary activity and induced a stronger anti-immunoglobulin response than F(ab′)2 antivenom.